2011
DOI: 10.1093/jaoac/94.1.224
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative PCR Method for Roundup Ready® Soybean: Interlaboratory Study

Abstract: Quantitative and qualitative methods based on PCR have been developed for genetically modified organisms (GMO). Interlaboratory studies were previously conducted for GMO quantitative methods; in this study, an interlaboratory study was conducted for a qualitative method for a GM soybean, Roundup Ready® soy (RR soy), with primer pairs designed for the quantitative method of RR soy studied previously. Fourteen laboratories in Japan participated. Each participant extracted DNA from 1.0 g each of the soy samples c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…The LODs of the two GM maize events and all GM soybean events, targeting P35S, tE9, and Cry1Ab/Cry1Ac, were lower than those of the previous methods. Among other of our previous reports using PCR, conventional PCR analyses showed that the LOD of RRS targeting a construct specific region was 0.1%, and the LOD of MON810 targeting P35S was 0.2% . We have also developed a real-time PCR array method for comprehensive GM detection .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The LODs of the two GM maize events and all GM soybean events, targeting P35S, tE9, and Cry1Ab/Cry1Ac, were lower than those of the previous methods. Among other of our previous reports using PCR, conventional PCR analyses showed that the LOD of RRS targeting a construct specific region was 0.1%, and the LOD of MON810 targeting P35S was 0.2% . We have also developed a real-time PCR array method for comprehensive GM detection .…”
Section: Resultsmentioning
confidence: 97%
“…The developed method was demonstrated to be rapid and cost-effective, and the LODs of the methods were at the same level as or lower than those in our previously reported qualitative detection method including LAMP analyses. 14,24,26 The LODs of the developed methods were equal to or less than 0.5% for all targets, indicating that the developed methods are available not only for Japan but also other countries or areas such as the EU, Australia, New Zealand, and Korea in terms of the level of GM content. Therefore, we conclude that the developed method would be applicable for monitoring the validity of the food labeling system in many situations, including on-site inspection.…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 93%
“…Cf was calculated as the ratio of the copy number of event-specific targets to the copy number of the endogenous gene. 21 The differences of quantification results among all eight participating laboratories were statistically analyzed. The mean Cf values from the eight laboratories ranged from 0.38 to1.37 with SD ranging from 0.04 to 0.262 and RSD rangingfrom 7.39 to 23.09% (Table 3).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…17−19 Two plasmid calibrants have been validated for the detection of Roundup Ready soybean event GTS-40-3-2 by interlaboratory ring trials. 20,21 Three other plasmid calibrants, ERM-AD413, ERM-AD415, and ERM-AD427, have also been certified and commercialized worldwide by IRMM. 11−13 International collaborative validation is the prerequisite step for proposing a CRM for a GMO.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation